1989
DOI: 10.1055/s-0038-1646581
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Haemostatic Factors in 16 European Laboratories: Quality Assessment for the Multicentre ECAT Angina Pectoris Study

Abstract: SummaryAs part of a European multicentre prospective study involving the measurement of a number of haemostatic factors, a quality assessment (QA) scheme was organized. This paper describes the preparation, design and results of the first Qa exercise, involving 16 European laboratories and 10 haemostatic assays. The design allowed the investigation, for each assay, of the variability between duplicates and the variability between days within each centre, and of the agreement between centres. A graphical presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
1
15
1
Order By: Relevance
“…Providing that the amount of thrombin added to maximize the FVIII activation is appropriate, this test might be more specific than the clotting assay. However, although it has been previously reported that chromogenic FVIII methods had a better reproducibility than clotting assays (Rosen et al, 1985;Tripodi & Mannucci, 1986;van Dieijen et al, 1987;Thompson et al, 1989), we did not find any significant differences in the intra-assay and run-to-run coefficients of variation between the two methods.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Providing that the amount of thrombin added to maximize the FVIII activation is appropriate, this test might be more specific than the clotting assay. However, although it has been previously reported that chromogenic FVIII methods had a better reproducibility than clotting assays (Rosen et al, 1985;Tripodi & Mannucci, 1986;van Dieijen et al, 1987;Thompson et al, 1989), we did not find any significant differences in the intra-assay and run-to-run coefficients of variation between the two methods.…”
Section: Discussioncontrasting
confidence: 90%
“…Therefore, it cannot be excluded that these tests can give falsely high results due to the activation of coagulation system during blood collection and/or storage conditions. The use of a clotting method to determine FVIII levels may lead to considerable variations, as the reproducibility of these assays has been shown to be very poor, especially at high FVIII concentrations (Rosen et al , 1985; Tripodi & Mannucci, 1986; van Dieijen et al , 1987; Thompson et al , 1989). Moreover, the different reagents and equipments used for clotting assays make them hard to standardize and the comparison of inter‐laboratory results difficult.…”
Section: Discussionmentioning
confidence: 99%
“…First, the assay of factor VIII itself may lead to considerable variation. 119 Together with vWF:Ag, factor VIII:C showed the highest between-duplicate (5.6%) and betweenday (15%) coefficients of variation. Most often, factor VIII is measured as factor VIII:C by using modifications of the activated partial thromboplastin time (1-stage assay).…”
Section: Should We Screen Patients With Thrombosis For High Factor VImentioning
confidence: 99%
“…This is of particular importance when considering the generalisability of findings to symptomatic patients awaiting CABG. Very few studies (with the possible exception of the European Concerted Action on Thrombosis and Disabilities study) 209 were designed with the purpose of assessing the incremental prognostic value of biomarkers. No studies were identified that reported the incremental prognostic value of biomarkers in relation to a clearly defined clinical decision.…”
Section: Systematic Review Of the Relevance Of The Literature Identifiedmentioning
confidence: 99%